Dynamic Variable Step Size LMS Adaptation Algorithms-Application to Adaptive Feedforward Noise Attenuation - Airimitoaie, Tudor-Bogdan; Vau, Bernard; Bismor, Dariusz; Buche, Gabriel; Landau, Ioan Dore (2024 European Control Conference (ECC), 2024)
The paper explores in detail the use of dynamic adaptation gain/step size (DAG) for improving the adaptation transient performance of variable step-size LMS (VS-LMS) adaptation algorithms. A generic form for the implementation of the DAG within the VS-LMS algorithms is provided. Criteria for the selection of the coefficients of the DAG filter which is required to be a strictly positive real transfer operator are given. The potential of the VS-LMS adaptation algorithms using a DAG is then illustrated by experimental results obtained on a relevant adaptive active noise attenuation system.